2016
DOI: 10.1089/hs.2016.0037
|View full text |Cite
|
Sign up to set email alerts
|

How Do Low-Literacy Populations Perceive “Dirty Bombs”? Implications for Preparedness Messages

Abstract: Potential terror events such as "dirty bombs" could have significant public health effects, but little is known about how low-literacy populations perceive dirty bombs, their trust in public health or government officials to provide credible information, and their willingness to comply with recommended actions. We surveyed 50 low-literacy adults from a large urban center; they were mostly members of ethnic minority groups. We used unique social marketing methods-perceptual mapping and vector message modeling-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Perceptual mapping was used to support an understanding and visualization of the elements that facilitate and impede LDKT decision making and to assess how dialysis patients view the process of asking a potential donor for a kidney by their self-reported health status. This technique is widely applied in advertising and marketing and has been used by the authors to assess various public health decisions (Bass et al, 2012;Bass et al, 2016a;Bass et al, 2016b;Bass et al, 2016c;Bass et al, 2018a;Bass et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Perceptual mapping was used to support an understanding and visualization of the elements that facilitate and impede LDKT decision making and to assess how dialysis patients view the process of asking a potential donor for a kidney by their self-reported health status. This technique is widely applied in advertising and marketing and has been used by the authors to assess various public health decisions (Bass et al, 2012;Bass et al, 2016a;Bass et al, 2016b;Bass et al, 2016c;Bass et al, 2018a;Bass et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Maps were then used to compare among clusters to assess differences and whether an overall strategy for possible targeted messages could be incorporated into a BMI report card targeted to urban parents. These methods are widely used in advertising and marketing and have been used by the authors to assess a number of decisions related to public health (Bass, Gordon, Ruzek, & Hausman, 2008; Bass et al, 2013; Bass, Muñiz, Gordon, Maurer, & Patterson, 2016; Bass, Gordon, et al, 2016; Bass, Wolak, et al, 2016; Bass et al, 2018; Gordon et al, 2009; Ruggieri et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Maps for segments of a population, either by demographic or by psychographic variables, can also be run for comparison and are important in understanding variability in the sample. This is an essential step for developing targeted and tailored messages (Bass et al, 2008; Bass et al, 2013; Bass, Gordon, et al, 2016; Bass, Muñiz, et al, 2016; Bass, Wolak, et al, 2016; Bass et al, 2018; Ruggieri et al, 2013; more details about the perceptual mapping techniques can be accessed at: https://sites.temple.edu/turiskcommlab/).…”
Section: Methodsmentioning
confidence: 99%
“…52 A series of studies demonstrated that acceptance of information during an incident was predicted by one's level of agent-specific knowledge, trust in the message source, 27,62 whether the disaster is assumed to have low potential to cause personal harm and being from a directly affected population. 28 Regarding information preferences of different subgroups, Bass 63 found low literacy (mostly ethnic minority) survey respondents fell into three categories based on their perceptions of information sources and anticipated adherence: those most likely to trust that information is accurate and to adhere to sheltering instructions despite believing that authorities are unlikely to provide them with the same level of support as they do others; those least likely to adhere or prepare out of distrust in authorities and their information and; those likely to adhere to sheltering instructions given by local, but not national sources.…”
Section: Perceived Credibility Of Information Sourcementioning
confidence: 99%